Literature review of the clinical features of sulfasalazine-induced drug reaction with eosinophilia and systemic symptoms/drug-induced hypersensitivity syndrome (DRESS/DIHS) - Liu, Ya; Wang, Danxia; Wu, Shiwei; Liu, Xiang; Xiao, Can (Frontiers in Pharmacology, 2024)
Background: Sulfasalazine (SSZ) is commonly prescribed for the treatment of ulcerative colitis, rheumatoid arthritis, and ankylosing spondylitis. However, it can also trigger a severe drug reaction known as Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) or Drug-Induced Hypersensitivity Syndrome (DIHS). This article aims to analyze the clinical characteristics of DRESS/DIHS induced by SSZ and provide evidence for clinical diagnosis, treatment, and prevention. Methods: We gathered relevant literature on SSZ-induced DRESS/DIHS published from January 1, 2005, to July 21, 2024, by searching both English and Chinese databases. Results: Thirty-nine patients (15 males and 24 females) were included in the study, with a median age of 47 years (range: 11-82 years). Following SSZ administration, the median onset time of DRESS/DIHS was 28 days (range: 10-60 days). These patients exhibited clinical symptoms such as fever (100%), rash (100%), digestive system responses (38.5%), and edema (35.9%). Organ involvement was observed in 38 patients, with commonly affected organs being lymph nodes (78.9%), liver (94.7%), kidney (15.8%), heart (13.2%), and lung (7.9%). All patients had hematological abnormalities, primarily eosinophilia (69.2%) and atypical lymphocytosis (35.9%). Additional hematological changes included agranulocytosis (5.1%), hemophagocytic syndrome (5.1%), and pancytopenia (2.6%). Virus reactivation occurred in 21 patients (53.8%). The primary treatment for DRESS/DIHS due to SSZ is the immediate cessation of the drug, followed by systemic corticosteroid administration. Alternative treatments such as cyclosporine, intravenous immunoglobulin (IVIG), mycophenolate mofetil, cyclophosphamide, and rituximab require further investigation to establish their efficacy. Conclusion: SSZ may lead to DRESS/DIHS. To make a conclusive diagnosis, healthcare providers should conduct a thorough assessment by examining the patient’s clinical presentation, conducting physical evaluations, and analyzing laboratory findings. Immediate discontinuation of SSZ is recommended, and corticosteroids are often considered an efficacious treatment for DRESS/DIHS.